2017
DOI: 10.1128/aem.02750-16
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Diversity and High Abundance of Putative Nitric Oxide Dismutase (Nod) Genes in Contaminated Aquifers and Wastewater Treatment Systems

Abstract: It has recently been suggested that oxygenic dismutation of NO into N 2 and O 2 may occur in the anaerobic methanotrophic "Candidatus Methylomirabilis oxyfera" and the alkane-oxidizing gammaproteobacterium HdN1. It may represent a new pathway in microbial nitrogen cycling catalyzed by a putative NO dismutase (Nod). The formed O 2 enables microbes to employ aerobic catabolic pathways in anoxic habitats, suggesting an ecophysiological niche space of substantial appeal for bioremediation and water treatment. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
68
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 39 publications
2
68
0
Order By: Relevance
“…In total, 61 nod OTUs with at least 50 sequences were classified based on 90% similarity on nucleotide level [7]. Representative sequences were used for phylogenetic analysis, revealing that almost all OTUs detected in this study were related to previously reported nod lineages [6], with most of them belonging to the nod "Aquifer cluster," 5 OTUs in the "NC10 cluster," and 1 OTU in the "Reactor cluster 1" (Fig. 2).…”
mentioning
confidence: 56%
See 2 more Smart Citations
“…In total, 61 nod OTUs with at least 50 sequences were classified based on 90% similarity on nucleotide level [7]. Representative sequences were used for phylogenetic analysis, revealing that almost all OTUs detected in this study were related to previously reported nod lineages [6], with most of them belonging to the nod "Aquifer cluster," 5 OTUs in the "NC10 cluster," and 1 OTU in the "Reactor cluster 1" (Fig. 2).…”
mentioning
confidence: 56%
“…The sample designations are the same as in Table 1 oxygenic denitrifiers was recently established [6,7], with which, evidence was obtained suggesting that oxygenic denitrifiers could be widespread and phylogenetically diverse [6,8]. However, the high diversity inferred from nod genes provided no clue to the actual identities of these novel oxygenic denitrifiers [6]. So far, the identification of oxygenic denitrifiers and analysis of their community structures solely depend on the length and quality of obtained nod sequences.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This process is usually coupled with alkane oxidation by a monooxygenase (Ettwig et al, 2012). Bacteria that harbour NOD in WWTPs are diverse and are especially abundant in systems with transient occurrence of NO 2 2 /NO 2 3 or hypoxia (Zhu et al, 2017). They also have been detected in activated sludge systems and anaerobic digesters from municipal WWTP (Ho et al, 2013).…”
Section: Denitrifying Anaerobic Methane Oxidizing Bacteria and Other mentioning
confidence: 99%
“…The abundance of anammox bacteria was quantified by targeting the hydrazine synthease beta-subunit (hzsB) gene with the primer set HSBeta396F and HSBeta742R (Wang et al, 2012). The qPCR of the n-damo putative NO dismutases (Nod) gene was performed with primers nod1446F and nod1706Rv2 (Zhu et al, 2016). The abundances of AOA and AOB were assessed by targeting the ammonia monooxygenase a-subunit (amoA) gene with the primer set archea-amoAF and archea-amoAR for archaeal amoA and amoAF and amoAR for bacterial amoA, respectively (Francis et al, 2005;Wang et al, 2011).…”
Section: Molecular (Q)pcr Assaymentioning
confidence: 99%